PENDIDIKAN ISLAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Yayat Suharyat; Agustina Agustina; Muzayyanah Yuliasih (Attadib: Journal of Elementary Education, 2018)
This research is motivated by the condition of Islamic Education as an important subject in the formation of noble values of students. Islam as a religion which is a system of belief and belief greatly influences actualization in the context of education. Formulation of the proposed problem is: "What is the role of Islamic Education in facing the paradigm shift of the 4.0 Industrial Revolution?" The expected goal of this research, is expected to be able to obtain a description of the role that must be fulfilled by Islamic Education in the face of changes in the industrial era 4.0. The results of the study show that the role of Islamic Education is very crucial in facing the changing times that are needed in determining the values of virtue that are the guidelines for future generations. The conclusion from this research is that every implementation and implementation of Islamic Education must be able to direct students to act based on morals which are stated in the Qur'an and Sunnah as well as on the agreement of the scholars.